Racial/ethnic differences in positive childhood experiences across a national sample - Crouch, Elizabeth; Radcliff, Elizabeth; Merrell, Melinda A.; Brown, Monique J.; Ingram, Lucy Annang; Probst, Janice (Child abuse & neglect, 2021)
•Little is known about racial/ethnic differences in positive childhood experiences.•Minority groups were less likely to experience many positive childhood experiences.•Absence of supportive factors may hinder children in healthy development. Examination of racial/ethnic differences in positive childhood experiences (PCEs) is needed, as the absence of supportive factors may hinder children from healthy processing and mitigation of adversity. The purpose of this study was to examine the prevalence of PCEs in a nationally representative sample of children and determine whether PCE exposure differed across race and ethnic groups. Data were drawn from the nationally representative 2017–2018 National Survey of Children’s Health (NSCH) (n = 33,747). Descriptive statistics and bivariate analyses were used in order to calculate frequencies, proportions, and unadjusted associations for each variable. Multivariable regression models were used to examine the association between race/ethnicity and PCEs. All racial-ethnic minority groups of children had a lower likelihood of mentorship, living in a safe neighborhood, or living in a supportive neighborhood, than their Non-Hispanic White counterparts. Non-Hispanic Black children had a lower likelihood of having a mentor for advice or guidance (aOR 0.50; 95 % CI 0.38−0.62), living in a safe neighborhood (aOR 0.62; 95 % CI 0.52−0.73), and living in a supportive neighborhood (aOR 0.75; 95 % CI 0.64−0.87) than Non-Hispanic white children. The information from this study highlights the negative disparities borne by racial/ethnic minority populations. Findings can be used to inform policymakers, program developers, and stakeholders on where to target interventions and how to bring together families and communities to not only confront adversity in childhood, but also to leverage community and family-level assets to create PCEs for all children.